The effect of brand awareness and brand image on purchasing decisions for Scarlett whitening products - Katerina, Angel; Simanjuntak, Anisa; Terenggana, Candra Astra; Tyra, Maria Josephine (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
Two factors influence consumers' decision to purchase a product, namely brand awareness and brand image. This study examines the significant influence of brand awareness and brand image on purchasing decisions for Scarlett Whitening products. Data used The data used is primary data. All consumers who know and have/are using Scarlett Whitening are the population in this research. The sample collected was 106 respondents. The sampling technique used was non-probability sampling, namely the purposive method (judgment sampling). Data was collected using an online questionnaire (google form) distributed through social media. The analysis technique used is validity and reliability testing, multiple linear analysis models to generate t-test results, F-test, and coefficient of determination. The findings of this study are brand awareness and brand image, both of which affect purchasing decisions positively and significantly. The results of this study imply that companies can increase efforts to build and increase brand awareness and a positive brand image